2015
DOI: 10.1111/dote.12332
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of staging laparoscopy in detecting peritoneal dissemination in patients with gastroesophageal adenocarcinoma

Abstract: Despite staging laparoscopy (SL) with peritoneal lavage is recommended in US Guidelines in patients with potentially resectable gastroesophageal adenocarcinoma, this procedure is not systematically proposed in French Guidelines. Therefore, we decided to analyze the results of systematic SL in patients considered for preoperative chemotherapy. From 2005 to 2011, 116 consecutive patients with distal esophagus, esogastric junction, and gastric adenocarcinoma ≥T3 or N+ without detectable metastatic dissemination b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Irino et al, Hosogi et al, Miki et al, Ishigami et al, Yamagata et al and Nakagawa et al reported the detection rate of P1 and/or CY1 as 47%, 45%, 53.4%, 42.7%, 46% and 51.6%, respectively. Results of these studies from Japanese institutions were almost similar (range: 42.7% to 53.4%), and higher than those from other countries (range: 7.8% to 40%) . The reason for this discrepancy was the difference in the indication for SL.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Irino et al, Hosogi et al, Miki et al, Ishigami et al, Yamagata et al and Nakagawa et al reported the detection rate of P1 and/or CY1 as 47%, 45%, 53.4%, 42.7%, 46% and 51.6%, respectively. Results of these studies from Japanese institutions were almost similar (range: 42.7% to 53.4%), and higher than those from other countries (range: 7.8% to 40%) . The reason for this discrepancy was the difference in the indication for SL.…”
Section: Resultsmentioning
confidence: 74%
“…Staging laparoscopy is considered a safe procedure carried out within one hour under general anesthesia. Some reported intestinal injury during SL . In many reports, there were no SL‐related complications (Table ), but the estimated SL‐related complication rate was 0.4% based on total accumulated data.…”
Section: Resultsmentioning
confidence: 99%
“…Auch bei makroskopisch unauffälliger Staging-Laparoskopie ohne Nachweis von peritonealen Metastasen ist beim lokal fortgeschrittenen Magenkarzinom oder Karzinom des ösophagogastralen Übergangs (AEG) mit einer positiven Zytologie zu rechnen [366]. Deshalb sollte die Peritoneallavage mit Zytologie ein integraler Bestandteil der diagnostischen Laparoskopie vor Therapieentscheid sein und in standardisierter Technik vorgenommen werden [367]. Die Ergebnisse von Patienten mit Magenkarzinom und positiver Zytologie in der Peritoneallavage unterscheiden sich derzeit durch diagnostische Methoden aufgrund der quantitativen und qualitativen Diversität der Tumorzellen.…”
Section: Hintergrundunclassified
“…Both modalities lack sensitivity to detect small peritoneal or liver metastases and may miss metastases in 13‐41% of patients . Diagnostic staging laparoscopy (DSL) is a staging modality that allows for direct visualization of the peritoneum, liver, and abdominal cavity, and can be performed when CT and EUS are negative or inconclusive in order to identify radiographically occult metastases …”
Section: Introductionmentioning
confidence: 99%